Estudo da diferença entre as curvas de título público prefixada em reais interna e externa brasileira - Costa, Daniel Barros Rodrigues (2008)
Since September 2005 Brazil government sells fixed reais debt on offshore market. Those bonds trade at a price significantly above similar onshore debt. This disparities remains if we consider the differences of costs and tax between onshore and offshore markets. In February 2006 Brazil government exempted foreign investor to pay income tax in local fixed income sovereign debt. This paper quantifies the difference between onshore and offshore brazilian local currency debt yield curve. The analysis is done assuming the point of view of the foreign investor after costs and taxes. We show that a large fraction of the variability of this difference is explained by demand for local currency (measured by exchange rate) and interest rate exposure (local market curve). With this model, we quantified the impact in onshore curve of the foreign investor income tax exemption to be 0.15%. Applying Granger’s causality test (GRANGER, 1969) it was not possible to refute that offshore fixed reais curve cause onshore one.